The effect of a community health worker intervention on public satisfaction: evidence from an unregistered outcome in a cluster-randomized controlled trial in Dar es Salaam, Tanzania - Elysia Larson; Pascal Geldsetzer; Eric Mboggo; Irene Andrew Lema; David Sando; Anna Mia Ekström; Wafaie Fawzi; Dawn W. Foster; Charles Kilewo; Nan Li; Lameck Machumi; Lucy Magesa; et al. (Human Resources for Health, 2019)
Abstract Background There is a dearth of evidence on the causal effects of different care delivery approaches on health system satisfaction. A better understanding of public satisfaction with the health system is particularly important within the context of task shifting to community health workers (CHWs). This paper determines the effects of a CHW program focused on maternal health services on public satisfaction with the health system among women who are pregnant or have recently delivered. Methods From January 2013 to April 2014, we carried out a cluster-randomized controlled health system implementation trial of a CHW program. Sixty wards in Dar es Salaam, Tanzania, were randomly allocated to either a maternal health CHW program (36 wards) or the standard of care (24 wards). From May to August 2014, we interviewed a random sample of women who were either currently pregnant or had recently delivered a child. We used five-level Likert scales to assess women’s satisfaction with the CHW program and with the public-sector health system in Dar es Salaam. Results In total, 2329 women participated in the survey (response rate 90.2%). Households in intervention areas were 2.3 times as likely as households in control areas to have ever received a CHW visit (95% CI 1.8, 3.0). The intervention led to a 16-percentage-point increase in women reporting they were satisfied or very satisfied with the CHW program (95% CI 3, 30) and a 15-percentage-point increase in satisfaction with the public-sector health system (95% CI 3, 27). Conclusions A CHW program for maternal and child health in Tanzania achieved better public satisfaction than the standard CHW program. Policy-makers and implementers who are involved in designing and organizing CHW programs should consider the potential positive impact of the program on public satisfaction. Trial registration ClinicalTrials.gov, EJF22802